Optymalna lokalizacja przedsiębiorstwa - Schärlig, Alain (Wydział Prawa i Administracji UAM, 1973)
The problem in which the author is interested can be defined as choice of location for activities that would secure them place of movement. Methods of two categories are used to solve the problem. Methods belonging under one of the categories are of continued and summary nature. Although they permit only of minimization of movement, they are useful. Weber problems in spatial economics where the author discusses in detail the solution of the problem by the method of successive approximations belong under that category. Methods belonging under the other category are of discrete type. They are more improved and more difficult in application than the former ones. Besides the methods of Pitagoras and René Opper, the graph and economic calculus method developed at present by C. Ponsard and the author himself is particularly exposed.
Optimum Location of an Enterprise